PERANCANGAN SISTEM WEB E-COMMERCE PENJUALAN KAOS - Sigit, Moch Sigit Sulaeman (Universitas Majalengka, 2021)
Kazastore is a company that sells plain t-shirts in the city of Bandung. Sales and marketing systems that are used today are still using the manual system. With that it is very necessary to have services to make it easier for customers to order products online. For this reason, the authors designed an online sales system at the Kazastore Company based on the web with the programming languages ​​PHP and MySQL, known as E-Commerce. This application is designed using the SDLC (System Development Life Cycle) method. With the hope that this application is of course to make it easier for customers to buy from Kazastore online only and where, customers can also see what product information and how the product details are available in Kazastore.